Prototype Sistem Informasi Registrasi Online Puskesmas (SIROP) : Puskemas Aurduri Kota Jambi - Aryani, Reni (LPPM Universitas Dinamika Bangsa, 2023)
This study aims to develop a prototype of the Community Health Center Online Registration Information System (SIROP) at the Aurduri Health Center, Jambi City. SIROP is a web-based system that is integrated with a database to optimize the patient registration process and improve access to health services at the puskesmas. The Aurduri Health Center as one of the health service units in Jambi City is tasked with providing basic health services to the community. However, the registration process is still manual, causing potential disruption to the efficiency and accessibility of health services. In developing this SIROP prototype, we focused on general patient registration modules, schedule management, and automatic queue numbering. Data for system development was collected through observation, interviews, and questionnaires to medical staff and patients in order to understand the needs and problems that exist in the ongoing manual registration process. After the prototype was successfully developed, a performance test was carried out using the application and Blackbox testing with the help of the Catalon Study software. It is hoped that with the adoption of the SIROP prototype, patient waiting times can be reduced and medical resources can focus on better health services